The diagnostic value of adenosine deaminase activity in the ascitic fluid of patients with tuberculous peritonitis - Voigt, Michael D (Department of Medicine, 2017)
This study was designed to: 1. Examine the diagnostic value of ADA levels in ascitic fluid, 2. Establish the sensitivity and specificity of this test in the diagnosis of tuberculous peritonitis, in a large number of patients, 3. Establish levels of adenosine deaminase activity which give the best discriminatory information in patients with ascites. 4. Determine what conditions may give rise to false positive or false negative results. 5. Finally, the study was designed to assess the relative diagnostic accuracy of previously used biochemical and haematological data, such as ascites total protein and white cell count. The diagnostic value of these tests alone, and combined with ADA activity in a descriminant analysis, was compared with the diagnostic accuracy of adenosine deaminase activity alone.